Rastros de imaginação lésbica: uma busca literária em "As Ondas", de Virginia Woolf e "Ara", de Ana Luísa Amaral - Gomyde, Monalisa Almeida Cesetti (2022)
The main purpose of this research was the weaving of a path towards women's literature on the love between women, in which the strength of the lesbian existence (RICH, 1980) present in the works is not ignored or misunderstood. For this, the concept of Lesbian Imagination, coined by Marylin Farwell (1988), was substantiated, expanded, and proposed as a possible reading practice, used, then, in the study of two literary works, Ara (2016) by Ana Luísa Amaral and The Waves (1931/2018) by Virginia Woolf. It started with an enquiry about the female creative process, if there would be something specific in it and in what ways the recognition of this possible specificity would affect the reading of female literary works, especially regarding the presence of the lesbian existence in such works. Thus, with the help of the definition of hermeneutic violence and symbolic clitoridictomy (GARRETAS, 2020) some of the faces of women's silence in patriarchy were portrayed and through the concept of the symbolic maternal order (MURARO, 1994) a route to the dizibility and the free feminine symbolic (IRIGARAY, 1980) was traced. In order to detail the lesbian existence, some narrative and political disputes around the name "lesbian" were presented, with special attention to the conceptualizations of lesbians themselves (CLARK, 1988; RICH, 1980; WITTIG, 1994). The practice of the Lesbian Imagination has been allocated within feminist literary theory as the lesbian dimension of Gynocriticism (SHOWALTER, 1981).